Sudden Death and ICD Implantation in Special Situations: Prinzmetal’s Angina - Chati, Gabrielle Lahoud; Porto, Fernando Mello; Gimenez, Daniel Fioravanti; Barbosa, Guilherme Viana; Lucena Neto, Adão Bento de; Cury Filho, Halim; Lima, José Marco de Nogueira (JOURNAL OF CARDIAC ARRHYTHMIAS, 2026)
The objective of this study was to report the case of a patient with Prinzmetal’s angina who experienced cardiac arrest due to ventricular fibrillation. The patient was successfully resuscitated, and underwent implantation of an implantable cardioverter-defibrillator (ICD) for secondary prevention. Data were collected through a review of medical records, analysis of diagnostic tests, and a literature review. This case highlights the importance of risk stratification and ICD implantation in patients with Prinzmetal’s angina and life-threatening arrhythmic events, ensuring appropriate management and reducing the risk of recurrence.